2013
DOI: 10.1002/jnr.23269
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity‐related gene 1 is important for survival of neurons derived from rat neural stem cells

Abstract: Plasticity-related gene 1 (Prg1) is a membrane-associated lipid phosphate phosphatase. In this study, we first investigated the role of Prg1 in the survival of neurons derived from rat neural stem cells (NSCs) using small interfering RNA (siRNA). Prg1 knock-down decreased the cell number. Interestingly, Prg1 knock-down increased genomic DNA fragmentation, suggesting the possible induction of apoptosis. Exogenously expressed Prg1 rescued the cells from death and restored the loss of 3-(4,5-dimethylthiazol-2-yl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In study on human tissue, PRG-1 was found differentially regulated in the substantia nigra of clinically and histologically confirmed epileptic seizures and Parkinson' s disease patients [37]. At present, studies on PRGs family mainly focus on neuropsychiatric diseases and nerve injuries such as epilepsy [34,38,39], schizophrenia [40,41], memory disorders [35], nerve trauma [42,43], sensory discrimination deficit [44,45], etc. Besides, PRG-1 may be involved in cancerogenesis because the target role of LPA in cancer [33,46].…”
Section: Ivyspringmentioning
confidence: 99%
“…In study on human tissue, PRG-1 was found differentially regulated in the substantia nigra of clinically and histologically confirmed epileptic seizures and Parkinson' s disease patients [37]. At present, studies on PRGs family mainly focus on neuropsychiatric diseases and nerve injuries such as epilepsy [34,38,39], schizophrenia [40,41], memory disorders [35], nerve trauma [42,43], sensory discrimination deficit [44,45], etc. Besides, PRG-1 may be involved in cancerogenesis because the target role of LPA in cancer [33,46].…”
Section: Ivyspringmentioning
confidence: 99%
“…Although there have been no conclusive studies on PLPPR-dependent neuronal survival or apoptosis, it has been reported that knockdown of PLPPR4 in neural stem cells decreases neuron viability in vitro , supposedly via induction of apoptotic death ( Hashimoto et al, 2013 ). It is noteworthy that the H253A mutant of PLPPR4, which disables the conserved LPA binding motif of PLPPRs and PLPPs ( Figure 1B ) and prevents PLPPRs from plasma membrane localization, cannot support PLPPR4-dependent neuronal survival ( Hashimoto et al, 2013 ). Whether this function is unique for PLPPR4 and whether it depends on LPA and LPARs remains to be studied.…”
Section: Phospholipid Phosphatase-related Proteins In Developmental G...mentioning
confidence: 99%
“…To date, studies on PRGs family have mainly focused on neuropsychiatric diseases and nerve injuries such as epilepsy (Ni et al, 2009;Trimbuch et al, 2009;Vogt et al, 2017), schizophrenia (Thalman et al, 2018;Vogt et al, 2016), memory disorders (Liu et al, 2016), nerve trauma (Hashimoto et al, 2013;Peeva et al, 2006), and sensory discrimination deficit (Cheng et al, 2016;Unichenko et al, 2016). We recently delineated a new physiological role for PRG-1 in chronic pain where we found that hippocampal PRG-1 relieves pain and depressive-like behaviors caused by bone cancer pain via P2X 7 R/PRG-1/PP2A pathway regulation of dendritic spine density in a cell-autonomous fashion (Liu et al, 2021a).…”
Section: Ll Open Accessmentioning
confidence: 99%